SHANK2 Mutations Result in Dysregulation of the ERK1/2 Pathway in Human Induced Pluripotent Stem Cells-Derived Neurons and Shank2(−/−) Mice - Lutz, Anne-Kathrin; Pérez Arévalo, Andrea; Ioannidis, Valentin; Stirmlinger, Nadine; Demestre, Maria; Delorme, Richard; Bourgeron, Thomas; Boeckers, Tobias M. (Frontiers in Molecular Neuroscience, 2021)
SHANK2 (ProSAP1) is a postsynaptic scaffolding protein of excitatory synapses in the central nervous system and implicated in the development of autism spectrum disorders (ASD). Patients with mutations in SHANK2 show autism-like behaviors, developmental delay, and intellectual disability. We generated human induced pluripotent stem cells (hiPSC) from a patient carrying a heterozygous deletion of SHANK2 and from the unaffected parents. In patient hiPSCs and derived neurons SHANK2 mRNA and protein expression was reduced. During neuronal maturation, a reduction in growth cone size and a transient increase in neuronal soma size were observed. Neuronal proliferation was increased, and apoptosis was decreased in young and mature neurons. Additionally, mature patient hiPSC-derived neurons showed dysregulated excitatory signaling and a decrease of a broad range of signaling molecules of the ERK-MAP kinase pathway. These findings could be confirmed in brain samples from Shank2(-/-) mice, that also showed decreased mGluR5 and phospho-ERK1/2 expression. Our study broadens the current knowledge of SHANK2-related ASD. We highlight the importance of excitatory-inhibitory balance and mGluR5 dysregulation with disturbed downstream ERK1/2 signaling in ASD which provides possible future therapeutic strategies for SHANK2-related ASD.